2020
DOI: 10.1155/2020/1804630
|View full text |Cite
|
Sign up to set email alerts
|

Histological, Histomorphometrical, and Biomechanical Studies of Bone‐Implanted Medical Devices: Hard Resin Embedding

Abstract: The growing incidence of degenerative musculoskeletal disorders as well as lifestyle changes has led to an increase in the surgical procedures involving implanted medical devices in orthopedics. When studying implant/tissue interface in hard materials (i.e., metals or dense plastics) and/or in large bone segments, the hard plastic embedding of the intact undecalcified tissue envelope with the implant in situ is needed. The aim of this work is to describe the advances and the possibilities of high-temperature m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
2
17
0
5
Order By: Relevance
“…In agreement with our proposal, Maglio et al 27) , processed large bone samples, with or without metal implants, with or without bone substitute materials, at room temperature (RT) and the use of a chemical fume hood throughout the procedure. We use similar embedding protocols, although we selected dibutyl phthalate instead of nonylphenol ethoxylate used by them.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with our proposal, Maglio et al 27) , processed large bone samples, with or without metal implants, with or without bone substitute materials, at room temperature (RT) and the use of a chemical fume hood throughout the procedure. We use similar embedding protocols, although we selected dibutyl phthalate instead of nonylphenol ethoxylate used by them.…”
Section: Discussionsupporting
confidence: 81%
“…The pre-polymerized MMA base, used in most protocols, was employed to prevent the formation of bubbles. It also promotes sample orientation 5,13,19,24,27) . We observed a complete reduction of tissue sections detachment at the deplasticization process when we used the combination of acid etched glass and Haurpt's adhesive over slide glass.…”
Section: Discussionmentioning
confidence: 99%
“…Different 2 and 3D imaging technologies have been recently developed to study the bone-biomaterial interface in the body. [54][55][56][57] In this study, we used different histology, immunohistochemistry, histomorphometry, 3D micro computed tomography (µCT), and small-angle X-ray scattering (SAXS) analyses to evaluate the tissue responses to the Mg alloys. We hypothesized that the results obtained from both 2 and 3D imaging technologies would be comparable.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, histological, histochemical and histomorphometric analyses were used. Bernhardt et al (2012) 48 and Maglio et al (2020) 49 reported histological imaging as the gold standard for analyzing bone formation around metallic implants, as this method allows for the detection of inflammatory and cellular changes that cannot be detected by radiographic examination alone.…”
Section: 35mentioning
confidence: 99%